2009
DOI: 10.1155/2009/958658
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interleukin-1βin Tumor Necrosis Factor-α-Induced Acute Pulmonary Inflammation in Mice

Abstract: We determined the role of interleukin-1β (IL-1β) signaling on tumor necrosis factor alpha-induced (TNF-α) lung neutrophil influx as well as neutrophil chemoattractant macrophage inflammatory protein (MIP-2) and KC and soluble TNF-α receptor (TNFR) levels utilizing wildtype (WT), TNF receptor double knockout (TNFR1/TNFR2 KO), and IL-1β KO mice after oropharyngeal instillation with TNF-α. A significant increase in neutrophil accumulation in bronchoalveolar lavage fluid (BALF) and lung interstitium was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…From another viewpoint, the additional inflammation after exposed to IL-1␤ protein might help to explain the progressive inflammation and pulmonary fibrosis even when human are no longer exposed to silica particles, irrespective of ongoing inflammatory responses stimulated by the repeating cycle of alveolar macrophage phagocytosis and cell rupture. It was supported by Saperstein and coworkers findings, which observed that IL-1␤ contributed to chemokine release and neutrophil recruitment in TNF-␣-mediated acute pulmonary inflammation in mice (Saperstein et al, 2009b). However, it is noteworthy that recombinant IL-1␤ protein did not directly induce endogenous IL-1␤ expression on differentiated THP-1 macrophages in this study.…”
Section: Discussionsupporting
confidence: 81%
“…From another viewpoint, the additional inflammation after exposed to IL-1␤ protein might help to explain the progressive inflammation and pulmonary fibrosis even when human are no longer exposed to silica particles, irrespective of ongoing inflammatory responses stimulated by the repeating cycle of alveolar macrophage phagocytosis and cell rupture. It was supported by Saperstein and coworkers findings, which observed that IL-1␤ contributed to chemokine release and neutrophil recruitment in TNF-␣-mediated acute pulmonary inflammation in mice (Saperstein et al, 2009b). However, it is noteworthy that recombinant IL-1␤ protein did not directly induce endogenous IL-1␤ expression on differentiated THP-1 macrophages in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, increases in these chemokines correlated with increased neutrophil recruitment. Interestingly, increased expression of MIP-2 and KC in the lung and BALF have been shown to be downstream of TNFα signaling (Saperstein et al 2009), which was not enhanced by ethanol pre-exposure in the lung in our model (Figure 4A). In contrast, hepatic TNFα mRNA expression and systemic levels of TNFα were enhanced by the combination of ethanol + LPS (Figure 3A).…”
Section: Discussionmentioning
confidence: 58%
“…Since the promoter region in the IL-1β gene contains binding motifs for AP-1 [35,36] inhibition of its activation will result in reduced IL-1β production. Having in mind that several studies have identified IL-1β as one of the major cytokines driving neutrophil accumulation in lung tissue [26][27][28][29]39,40], inhibition of AP-1 activation and consequent IL-1β production by alveolar macrophages seems to be a sufficient and likely mechanism by which azithromycin reduced neutrophil accumulation in the lungs following LPS challenge (concept summarized in Fig. 9).…”
Section: Discussionmentioning
confidence: 98%